2018
DOI: 10.1093/ejcts/ezy202
|View full text |Cite
|
Sign up to set email alerts
|

Aortic valve replacement using the Freedom SOLO stentless bioprosthesis: clinical and haemodynamic performance in 625 patients at medium-term follow-up

Abstract: The Freedom Solo stentless aortic valve has proved to be safe, with excellent clinical and haemodynamic results. Structural valve degeneration and explantation occur infrequently, illustrating good durability in the medium term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
1
0
2
Order By: Relevance
“…Độ tuổi trung bình của bệnh nhân trong nghiên cứu của chúng tôi là 62,8 ± 6,1 tuổi, trẻ hơn so với độ tuổi trung bình ở nghiên cứu về phẫu thuật thay van Freedom Solo của các tác giả khác trên thế giới [4], [5],. Có thể nguyên nhân vì phần lớn các nghiên cứu đó đều từ 2018 trở về trước nên áp dụng khuyến cáo khi thay van nhân tạo sinh học cho bệnh nhân trên 70 tuổi một cách thường quy [3].…”
Section: Bàn Luậnunclassified
“…Độ tuổi trung bình của bệnh nhân trong nghiên cứu của chúng tôi là 62,8 ± 6,1 tuổi, trẻ hơn so với độ tuổi trung bình ở nghiên cứu về phẫu thuật thay van Freedom Solo của các tác giả khác trên thế giới [4], [5],. Có thể nguyên nhân vì phần lớn các nghiên cứu đó đều từ 2018 trở về trước nên áp dụng khuyến cáo khi thay van nhân tạo sinh học cho bệnh nhân trên 70 tuổi một cách thường quy [3].…”
Section: Bàn Luậnunclassified
“…Previous mid-and long-term studies have shown immediate and sustainable improvement in hemodynamics, which contributes to the normalization of the left ventricular mass index. Freedom Solo® stentless bioprostheses have also presented their durability compared to currently available bioprostheses [2,3]. The Freedom Solo® valve has been used for aortic valve replacement (AVR) in the Cardiovascular Institute, Bach Mai Hospital since 2013.…”
Section: Introductionmentioning
confidence: 99%
“…13 Nghiên cứu của Thalman M. với 616 bệnh nhân thì mổ lại sớm do chảy máu chiếm 4,5%. Tuy nhiên, trong nghiên cứu này tác giả cũng có 2 bệnh nhân hở cạnh van phải mổ lại 14.…”
unclassified